Experimental and simulation study of the impact of increased photovoltaic integration with the grid - Shafiullah, G.; Oo, A.; Ali, A.; Wolfs, Peter; Stojcevski, A. (American Institute of Physics, 2014)
The abundance, availability, and climate-friendly characteristics of solar photovoltaic (PV) energy encourage nations around the globe to adopt it to assist in overcoming global warming as well as build a sustainable society for the future. The intermittent nature of solar energy generation and the associated power electronic inverters with connected consumer loads creates a number of potential challenges in integrating large-scale PV into the grid that affects power quality of the distribution networks. This paper investigates the impacts of varying PV integration into the grid through experimental and simulation studies. Initially, several experiments were conducted with varying PV penetration and load conditions using the Renewable Energy Integration Facility at CSIRO, Newcastle, Australia. Later, a simulation model was developed that mimics the experimental facility used at CSIRO to investigate the adverse impacts on integrating large-scale PV into the grid using the power system simulation software PSS Sincal. Experimental and simulation analyses clearly indicate that integration of PV into the grid causes power quality issues such as voltage instability, harmonic injection, and low power factor into the networks and the level of these impacts increases with the increase of PV penetration. © 2014 AIP Publishing LLC.